Marketing strategy and failure of Forever 21. (What is the reason behind Forever 21’s failure?) - Mekhruza Vafokulova; Umidjon Juraev (Genius Journals, 2022)
The current research analyzes marketing strategy of one of the famous brands Forever 21. Moreover, in this work the failure of this company is broadly discussed along with some internal and external analysis of the company with cases. The company marketing is compared with major competitors. The brand analysis is done through researching some major problems and at the end of the analysis, some proposed solution is come up.
Keywords: Forever 21; strategy; business; marketing